(untitled) (Diversity Research: Journal of Analysis and Trends, 2023)
The article considers the concept of inclusive education, which provides for the joint education of healthy students and students with disabilities, teaching tools for disabled people in vocational education, used to teach students with physical disabilities, speech impairments (dyslexia), hearing and vision.